Humour without Pathos of Internet Memes in the Context of Online Visual Communication (University of Bucharest Review. Literary and Cultural Studies Series, 2025)
In this article we focus on internet memes that have become an important genre of online communication, as internet users have created a new visual language: not only in form, but also in meaning (often very satiric). Internet memes relate to the Web 2.0 phenomenon, where users can access hundreds of meme templates, images, or short videos, and can assign them a specific meaning. The aim of this article is to theoretically define the “memetic visual language” with specific background, forms, and rules for creating and decoding it. In the empirical part of paper, we present a selection of examples put forward by the Slovak project ZOMRI, meant to demonstrate without pathos, but with humour, the power of internet memes to depict the personality of Slovak president Zuzana Caputova.
Keywords: internet meme; visual communication; online communication; visual language; virtual space; Zomri